Ethnic minority students’ attitudes and experiences with Mobile English Learning Resources in Qinghai: an Activity Theory analysis - Li, Danyang; Joseph Jeyaraj, Joanna; Razali, Abu Bakar (Taylor and Francis, 2025)
This qualitative study explores how ethnic minority university students in Qinghai, China, engage with Mobile English Learning Resources (MELRs) amid linguistic, cultural, and institutional constraints. Guided by Activity Theory (AT) and analysed using reflexive thematic analysis (RTA), the study drew on interviews and reflective journals. The participants were eight first-year non-English-major undergraduates, all Tibetan L1 speakers, from Tibetan, Mongolian, and Tu ethnic backgrounds. Two interconnected themes were developed: Empowerment within Frustration and Unequal Foundations and Missing Scaffolds. While students appreciated the flexibility and authentic exposure offered by MELRs, their engagement was often constrained by curriculum misalignment, limited digital experience, and a lack of sustained instructional and peer support. Through the lens of AT, the study identified four secondary contradictions within the activity system: between tools and subjects, rules and tools, community and tools, and division of labour and tools. Rather than attributing difficulties to individual shortcomings, the findings foreground systemic tensions shaping mobile learning experiences. The study highlights the importance of responsive, scaffolded, and contextually aligned mobile learning practices in supporting students from multilingual and under-resourced regions.